1974
DOI: 10.1677/joe.0.0600075
|View full text |Cite
|
Sign up to set email alerts
|

Chorionic Gonadotrophin in the Human Placenta in Relation to the Sex of the Foetus at Term

Abstract: Human chorionic gonadotrophin (HCG) was assayed by biological and radioimmunological methods in 40 human term placentae. It was found that the concentration of HCG per g and per placenta was lower when the sex of the foetus was male than when it was female. This difference is significant (P < 0\m=.\005) and applies to the results obtained both in the biological and the radioimmunological assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

1974
1974
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
2
8
1
Order By: Relevance
“…The results of the present investigation do agree with those previously published in which CG was found in term placentae from marmosets and rhesus monkeys [Hobson, 1972;Hobson and Wide, 1972]. The concentration of biologically active CG in ape and monkey placentae was, with the exception of the marmoset and lemur, within the range for human placentae at term [Hobson and Wide, 1974], The higher CG concentration in the placenta from one orang-utan, obtained early in pregnancy, is similar to that of man, where the highest concentrations of CG in placental tissue are also found early in gestation [Diczfalusy, 1953;Hobson, 1972]. In all the extracts from term pla centae the CG activity was higher in the bioassay.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present investigation do agree with those previously published in which CG was found in term placentae from marmosets and rhesus monkeys [Hobson, 1972;Hobson and Wide, 1972]. The concentration of biologically active CG in ape and monkey placentae was, with the exception of the marmoset and lemur, within the range for human placentae at term [Hobson and Wide, 1974], The higher CG concentration in the placenta from one orang-utan, obtained early in pregnancy, is similar to that of man, where the highest concentrations of CG in placental tissue are also found early in gestation [Diczfalusy, 1953;Hobson, 1972]. In all the extracts from term pla centae the CG activity was higher in the bioassay.…”
Section: Discussionsupporting
confidence: 93%
“…They have been com¬ pared with those of a previous investigation on term (37-41 weeks gestation) placentae (Hobson & Wide, 1974). The results of both investigations were converted to logarithmic values and their means and S.D.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the amount of human chorionic gonadotrophin (HCG) present in serum (Brody & Carlström, 1965), urine (Danielsson, 1965), serum and amniotic fluid (Crosignani, Nencioni & Brambati, 1972), and term placentae (Hobson & Wide, 1974) was related to the sex of the foetus. This relationship -significantly lower levels of HCG when the conceptus was male than when it was female -seems to be true for serum and urinary HCG in late pregnancy only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since regulation of HCG secretion is incompletely understood -albeit androgens [39][40][41] and pros taglandins [42] might play a role -this question is difficult to answer. According to Belisle et al [29], HCG in serum is 4-to 5-fold below normal values in women who subsequently start to bleed.…”
Section: Discussionmentioning
confidence: 99%